2009
DOI: 10.1111/j.1365-2222.2008.03121.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of omalizumab and specific immunotherapy is superior to immunotherapy in patients with seasonal allergic rhinoconjunctivitis and co‐morbid seasonal allergic asthma

Abstract: Combination of omalizumab with SIT for treatment of patients with SAR and co-morbid SAA was safe and reduced the symptom load in a statistically significant and clinically meaningful manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(177 citation statements)
references
References 37 publications
1
165
0
11
Order By: Relevance
“…Meta-analyses show that this treatment could be beneficial in pollen-induced rhinitis and asthma, but state that more investigations are needed to determine its efficacy in house dust mite allergy [70]. Recent studies found that adding anti-IgE therapy to SIT was significantly better at reducing symptoms of both seasonal allergic rhinitis [71] and asthma when compared with SIT alone [72], in addition to providing greater safety in adults as well as in children [73]. However, many guidelines consider SIT as a marginal treatment for asthma, although it is suggested for the types of allergic rhinitis mentioned earlier.…”
Section: Treatmentmentioning
confidence: 99%
“…Meta-analyses show that this treatment could be beneficial in pollen-induced rhinitis and asthma, but state that more investigations are needed to determine its efficacy in house dust mite allergy [70]. Recent studies found that adding anti-IgE therapy to SIT was significantly better at reducing symptoms of both seasonal allergic rhinitis [71] and asthma when compared with SIT alone [72], in addition to providing greater safety in adults as well as in children [73]. However, many guidelines consider SIT as a marginal treatment for asthma, although it is suggested for the types of allergic rhinitis mentioned earlier.…”
Section: Treatmentmentioning
confidence: 99%
“…In conjunction with s.c. injection using aeroallergens, omalizumab improved the tolerability of dose escalation while retaining and perhaps improving the long-lasting benefits of immunotherapy (83)(84)(85)(86)(87). Two small, uncontrolled studies of omalizumab combined with rush food oral immunotherapy, where dose escalation was performed at a more rapid pace than usual using either peanut or milk, have recently been published.…”
Section: Pathophysiology Of Food Allergymentioning
confidence: 99%
“…71,72 Recent studies have demonstrated efficacy of omalizumab in patients with more severe asthma, and in pooled analyses of several large clinical trials, omalizumab significantly reduced asthma exacerbations (by 38%), emergency department visits (by 61%) and hospital admissions (by 52%) and unscheduled doctor visits (by 47%) when compared to control subjects. 73,74 Omalizumab has also been studied as a treatment for other allergic diseases including allergic rhinoconjunctivitis, 75,76 as adjunctive therapy with allergen immunotherapy, 77,78 and as a treatment for chronic urticaria and angioedema, [79][80][81][82] atopic dermatitis, 83,84 allergic bronchopulmonary aspergillosis, 85,86 Churg-Stauss syndrome 87,88 and latex allergy. 89 Further study is ongoing; none of these conditions are approved indications for use of this drug.…”
Section: Promoting T H 1 Cytokinesmentioning
confidence: 99%